A bibliometric Odyssey through Guidance and Counseling Research (1939-2023) - Inayah, Apriliana Rifatin; Maksum, Muh. Nur Rochim; Anshori, Ari; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2023)
This study employs a scientometric approach to map the development and direction of research in guidance and counseling, drawing insights from publications indexed in the Scopus database. Covering the period from 1939 to 2023, the analysis encompasses all relevant journals within the platform. Utilizing a combination of Excel and R/R-Studio, the research delves into the data, while VOSviewer serves as a visual tool to explore the co-occurrence of keywords and document citations. The initial search yielded 5671 publications that aligned with the established criteria regarding function, subject area, and relevance. Key findings from the analysis reveal a remarkable annual growth rate of 9.26% in guidance and counseling research, reaching a peak in 2022. The United States emerges as the leading contributor in terms of publications, with Harvard University boasting the most affiliated publications. Among individual researchers, Chan, F stands out as the most prolific author in the field. It's crucial to acknowledge that the bibliometric analysis in this study was confined to the Scopus database. Future research would benefit from incorporating additional national and international databases for a more comprehensive understanding of the field. Ultimately, this study offers a valuable snapshot of the existing literature accessible to education researchers interested in guidance and counseling, paving the way for further exploration and innovation in this crucial domain.